Legal Reconstruction of The Hexsa Helix Synergy and Collaboration Model Mainstreaming Child Rights (PUHA) In The Implementation of Child Friendly District/Cities Programs - Susanto, Fransiska Ayulistya; Purnamaningtyas, Anindita; Widagdo, Setyo; Arrsa, Ria Casmi (Institute of Research and Community Service, University of Brawijaya, 2022)
The Government's commitment to fulfilling and mainstreaming Children's Rights (PUHA) is carried out to realize the goals of national development, namely advancing general welfare and educating the nation's life as mandated by the fourth paragraph of the Preamble of the 1945 Constitution of the Republic of Indonesia which explicitly states that the State exists in order to protect all of Indonesia's bloodshed, promoting public welfare and educating the life of the nation. Furthermore, the commitment referred to is also based on the constitutional basis as set forth in the provisions of Article 28B paragraph (2),